PENGEMBANGAN UMKM SEBAGAI PENGUATAN EKONOMI KERAKYATAN DI KOTA BUKITTINGGI (Studi Kasus: Industri Kerupuk Sanjai) - Yeniwati, Yeniwati (Jurnal Kajian Ekonomi, 2015)
This study aims the problems faced by home industry kerupuk Sanjai in the City of Bukittinggi to improve local economy. This study was conducted in March 2015 through a survey method (observation) with random purposive sampling technique. The sample in this study as many as twenty-six home industry Kerupuk Sanjai in Bukittinggi. This research found home industry Kerupuk Sanjai in Bukittinggi city is still traditional both in the production process, packaging and marketing system. So that the necessary cooperation with the relevant agencies in order to create innovation and creativity to improve quality and productivityÂ  as well as a broader marketing reach.Â Keywords: production, packaging, marketing system